EXPLORING LANGUAGE STYLES IN THE FILM UGLIES (2024): A SOCIOLINGUISTICS PERSPECTIVE - Daulay, Olga Adelia; Rosa, Rusdi Noor; Yusuf, Muhammad (Universitas Islam Sumatera Utara (UISU), 2025)
This study investigates the use of language styles in the film Uglies (released in 2024) by applying Joos’ (1967) classification of language styles (frozen, formal, consultative, casual, and intimate) and Holmes’ (2013) framework of social factors influencing the choice of language styles, including participants, setting, topic, and function. Using a qualitative approach with content analysis as the research design, this study took the data from the English subtitled transcripts of the film officially released by Netflix. The findings reveal that the casual style is the most dominant, followed by the intimate and consultative styles, reflecting the film’s focus on adolescent characters and peer relationships in informal and emotionally driven contexts. The formal style appears in institutional interactions, while the frozen style is notably absent, due to the lack of ceremonial or ritualistic settings in the narrative. Analyzing language in dystopian fiction is significant because it reveals how imagined societies construct power, identity, and resistance through communication. This study highlights the close relationship between language styles and social factors, demonstrating how linguistic choices reflect the dynamics of participant relationships and communicative functions in the film.